Bioaccumulation of heavy metals and metallothionein effects on reproductive biology of Asian Swamp eel (Monopterus albus Zuiew, 1793) in paddy fields in Tumpat, Kelantan, Malaysia - Sow, Ai Yin (2016)
The current application of excessive agrochemical fertilizers during the four paddy seasons could potentially elevate the concentration levels of Zn, Cu, Cd, Ni and Pb in paddy soils. Hence, concentrations of Zn, Cu, Cd, Ni and Pb in paddy soils and Asian swamp eel, Monopterus albus, were evaluated to determine the availability, distribution, overall classification and risk associated with application of agrochemical fertilizers and pesticides introduced by rice farmers. A four step sequential extraction technique (SET) was conducted to establish the speciation, mobility, availability and origin of heavy metals such as zinc, copper, cadmium, nickel and lead. These four fractions are termed as exchangeable (EFLE), acid-reducible, oxidisableorganic and resistant fractions in the paddy soil. Nine tissues of Asian swamp eel were selected, namely, gills, liver, kidneys, digestive tract, stomach contents, gonads, bone, skin and muscle; which were digested using the acid digestion method. In comparison to the values of average shale of the studied metals, total Pb and Cd were higher than the shale values, whereas the total Zn, Cu and Ni concentrations were found to be below the values. Generally, most of the metals studied were significantly associated with the resistant fraction, followed by oxidisable-organic and acid-reduction fractions. This indicates that the paddy soils of Tumpat are naturally rich with the metals studied. Meanwhile, the least average partitioning patterns in EFLE in paddy seasons indicate low Zn, Cu, Cd, Ni and Pb mobility. Among the metals studied, availability of average Cd and Pb levels was found to be abundant in most seasons based on enrichment factors and contamination factors. However, none of the studied metal concentrations in the paddy soils were as high as the toxic effect threshold (TET) value. Since Asian swamp eel is a long-lived organism, the longer the exposure to those pollutants, the higher the concentrations of metals were bio-accumulated into it. Levels of Zn, Cu, Cd, Ni and Pb in the stomach contents were found to be higher than other tissues studied. Muscle and skin were shown to have the least heavy metal concentrations. To evaluate the health risks to the Malaysian population through consumption of Asian swamp eel, daily intakes and target hazard quotient of heavy metals were estimated on the basis of the concentrations of heavy metals in muscle and skin of Asian swamp eel. Based on the estimated daily intake and THQ of Cd and Pb in skin and muscle in 2011 and 2012, the results suggest that Cd and Pb in skin and muscle of Asian swamp eel was polluted by Cd and Pb, which have higher risk to be consumed. Metallothionein (MT) concentrations in gills, liver and muscle tissues of M. albus were determined to assess the biological response of Asian swamp eel to the level of some metals. The concentrations of Zn, Cu, Cd, Ni and Pb (μg/g wet weight) in the tissues studied were correlated with MT contents. MT concentrations were found to be high in the liver, gills and muscles during plowing, growing, and harvesting seasons. However, a significant correlation (p < 0.01) was found between MTs concentrations in liver and Zn metals. No correlations were found between MTs contents in gills and muscle with the studied metals. In this study, the gonadal histological procedure was made as a basis for sex determination in Asian swamp eel, M. albus. Thirty-two females, three males and two intersexes of Asian swamp eel were considered. The presence of a high number of matured oocyte 3 and 4 during plowing and seedling seasons have shown that these seasons could be considered as breeding seasons for Asian swamp eels. The availability of food and nutrients (agrochemical fertilizers) were attributed to the ovarian development of Asian swamp eel. In conclusion, the concentrations of Zn, Cu, Cd, Ni and Pb in paddy soils varied with paddy cycles in 2011 and 2012. The presence of Zn, Cu, Cd, Ni and Pb in Asian swamp eels’ tissues indicates that these eels have the ability to accumulate and partially remove the heavy metals which required future research study.